Interrater Reliability and Age-Based Normative Values for Radiographic Indices of the Ankle Syndesmosis in Children - Nikita Lakomkin, BA; Peter D. Fabricant, MD, MPH; Aristides I. Cruz, Jr., MD; Christopher M. Brusalis, BA; Nancy A. Chauvin, MD; J. Todd R. Lawrence, MD, PhD (JBJS Open Access, 2017)
Background:. While recent research has investigated the normative values, discriminative capacity, and interrater reliability of radiographic indices for the evaluation of the syndesmosis in adults, no such data exist for children. The purposes of the present study were (1) to determine the interrater reliability of common radiographic measures of syndesmosis and deltoid ligament competency in children and (2) to establish age-based normative values. Methods:. A consecutive series of patient radiographs from a Level-I pediatric trauma center were identified and were used to create an age and sex-balanced cohort of 282 patients. Subjects between 2 and 17 years of age were randomly selected from a pool of patients who had a complete 3-view (anteroposterior, lateral, and mortise) radiographic ankle series and a final diagnosis without osseous or ligamentous injury. Eight age and sex-balanced groups were created for analysis. Three independent raters evaluated all radiographs and recorded radiographic indices that are commonly used for the evaluation of ankle trauma: width of medial clear space, width of superior clear space, tibiofibular clear space, tibiofibular overlap, and medial clear space/superior clear space ratio. Interrater reliability was calculated with use of the intraclass correlation coefficient (ICC); means and standard deviations were used to report age-group normative values. Results:. Two hundred and eighty-two patients (mean age [and standard deviation], 9.6 ± 4.6 years) were analyzed. The superior clear space and tibiofibular overlap demonstrated excellent interrater reliability (ICC = 0.915 and 0.964, respectively), the medial clear space and tibiofibular clear space demonstrated substantial agreement (ICC = 0.656 and 0.635, respectively), and the medial clear space/superior clear space ratio demonstrated moderate agreement (ICC = 0.418). The medial clear space could not be reliably measured until the age of 8 years because of insufficient ossification of the medial malleolus. Tibiofibular overlap demonstrated a linear increase over time, ranging from −1.4 mm in 2 and 3-year-old patients to 6.7 mm in 16 and 17-year-old patients (R2 = 0.995). Normative values varied by age and sex. Conclusions:. The medial clear space and medial clear space/superior clear space ratio could not be reliably assessed for children under 8 years of age and were thus characterized by suboptimal interrater reliability. Tibiofibular overlap had excellent interrater agreement, changed predictably with skeletal growth, and may be useful for future research as well as the clinical assessment of pediatric ankle injuries to guide clinical decision-making. Level of Evidence:. Diagnostic Level III. See Instructions for Authors for a complete description of levels of evidence.